American Institutions For The Feeble-Minded, 1876-1916 - Jirik, Katrina (My University, 2019)
Between 1876 and 1916, American institutions for the feeble-minded became an established part of the landscape and reflected important educational, social, medical, and scientific shifts during that period. This dissertation traces attitudes toward those deemed feeble-minded and the institutions that housed them by investigating the voices of people, organizations, and state governments that have not been well explored previously and identifying the particular influences that shaped them. The Association of Medical Officers of American Institutions of Idiotic and Feeble-minded Persons (AMO) formed in 1876 as the professional organization for institution superintendents and expanded its membership over the years to encompass other professionals with an interest in feeble-mindedness. It strove to become the repository of all things related to feeble-mindedness with its members seen as the recognized experts in the field. From small private establishments before the Civil War, these institutions expanded rapidly in the last quarter of the nineteenth century. Not only did the number of institutions increase, but the number of residents in the institutions and thus the size of the institutions to house them also grew significantly. While the establishment of pre-Civil War institutions had relied on philanthropic efforts and the advocacy of superintendents, the post-Civil War institutions were usually state funded and relied on the advocacy and social capital of prominent societal leaders. Between 1890 and 1900, the well-established institutions consolidated both the authority of those providing care and the functions of the institutions; in the process they moved from small residential schools to large, congregate, and increasingly, custodial institutions. The beginning of the twentieth century, from 1900 to 1916, brought new issues to the forefront. Compulsory school attendance laws, new understandings of heredity, and eugenics all pushed administrators and sponsors to reconsider the previous conceptions of care for the feeble-minded. Throughout these decades, superintendents, parents, educators, legislators and even members of the general public became engaged in the definition, growth, and influence of these institutions. It was not a static process; all these entities worked in concert with, and, sometimes, in opposition to, with each other.
University of Minnesota Ph.D. dissertation. May 2019. Major: History of Science, Technology, and Medicine. Advisors: Sally Kohlstedt, Jennifer Gunn. 1 computer file (PDF); vii, 288 pages.
Keywords: custodial care; education; feeble-minded; institutions; parents; United States